PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING ( CTL ) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 011 BUKIT KAPUR - Yonhaili '; Gustimal Witri Witri; Hendri Marhadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This  study  aims  to  improve  learning  outcomes  Mathematics  Elementary School  fourth  grade  students  with  the  application  of   011  Bukit Kapur approaches Contextual  Teaching  and Learning  ( CTL ).  This research  is a  form  of  class  action  research (PTK). The research instrument consists of learning tools and observation sheet activities of teachers and students during the learning process. To determine the students' learning outcome Mathematics conducted daily test after completing any one cycle. Based on the research that has been conducted through two cycles,  the  average  teacher in the second cycle of activity has increased  compared  with  the  cycle  of  I . At  the first  meeting of   the  first  cycle of the average activity of 68.75 % in the category of teachers is quite perfect, at the second meeting of teachers increased activity 75 % in both categories. At the first meeting of the second cycle of teacher activity increased to 90.63 % with very good category, at the second meeting increased compared to the first cycle of the first meeting, the second and the first meeting of the second cycle with an average of 93.75 % of teacher activity with very good category . For the  first  meeting  of  the  student  activity  first cycle  the  average  activity  of  68.75  %  students  with  enough  categories, at  the  second   meeting   of   the  first cycle of the average student activity increased to 71.88 % with both categories. At the first meeting of   the  second   cycle  of  the  average   student   activity    increased  to   90.63 %   with very good    category,  and   at   the   second  meeting  of  the  second  cycle has  increased at a previous meeting that is 93.75% with very good category. Keywords: CTL approach. Mathematics Learning Outcomes